STEM-09. INTRINSIC TUMOR PLASTICITY IN GLIOBLASTOMA ALLOWS FOR RECREATION OF STEM LIKE-STATES AND EFFICIENT TUMOR CELL ADAPTATION TO NEW MICROENVIRONMENTS. (11th November 2019) - Golebiewska, Anna; Dirkse, Anne; Buder, Thomas; Yabo, Yahaya A; Muller, Arnaud; Nazarov, Petr V; Bjerkvig, Rolf; Skupin, Alexander; Poovathingal, Suresh K; Herold-Mende, Christel; Voss, Anja; Deutsch, Andreas; et al.
Abstract: BACKGROUND: Cellular heterogeneity is a hallmark of numerous cancer types, including Glioblastoma (GBM). Cancer stem cells (CSC) have been accounted for the generation of phenotypic heterogeneity and tumor progression in GBM. Recent data, however, suggest that CSCs may not represent a stable entity and intrinsic plasticity plays a key role in tumor adaptation to changing microenvironments. The question arises whether CSCs are a defined subpopulation of GBM or whether they represent a cellular state that any cancer cell can adopt. METHODS: We interrogated intra-tumoral phenotypic heterogeneity at the single cell transcriptomic and proteomic level in GBM biopsies, patient-derived stem-like cultures and orthotopic xenografts (PDOXs). Tumor cell subpopulations, classified based on their expression of four proposed stem cell markers (CD133, CD15, A2B5 and CD44), were FACS isolated and functionally characterized under various microenvironmental conditions. Mathematical Markov modelling was applied to calculate state transitions. RESULTS: GBM patient biopsies, PDOXs and stem-like cell cultures displayed remarkable stem cell-associated intra-tumoral heterogeneity. However independent of marker expression, all analysed tumor subpopulations carried stem-cell properties and recreated phenotypic heterogeneity. Mathematical modeling revealed a different propensity in reforming heterogeneity over time, which was independent of the proliferation index but linked to in vivo tumorigenic potential. Although GBM subpopulations varied in their potential to adapt to new environments, all were able to reach a steady state microenvironment-specific equilibrium. CONCLUSIONS: Our results suggest that phenotypic heterogeneity in GBM results from intrinsic plasticity allowing tumor cells to adapt to changing microenvironmental conditions. Cellular states are non-hierarchical, reversible and occur via stochastic state transitions, striving towards a microenvironment-instructed equilibrium. Our data provides evidence that CSCs do not represent a defined clonal entity, but rather a cellular state determined by environmental conditions, which has implications for the design of treatment strategies targeting CSC-like states.